Securitization of Cross-border Refugee Forced Migration in Indonesia - Zayzda, Nurul Azizah (Law Research Review Quarterly, 2017)
Securitization of migration refers to the phenomenon of attaching the issue of migration to the issue of national security. This concept has evolved since Western countries such as Europe and the United States have imposed restrictions on those who migrate through selective immigration policies, strict border security. Basically migration securitization is not just about making migration organized; it also contains symbolic processes that create or reinforce rhetoric regarding the exclusivity of the political community. In Indonesia, the securitization of migration lies in the policies and rhetoric that is disseminated to the public domain regarding the migration of foreign nationals into Indonesian territory. This is demonstrated by the use of immigration detention centers to hold immigrant asylum seekers, the implementation of the Bali Process on People Smuggling, Trafficking in Persons and Related Transnational Crime and the Lombok Treaty with Australia, as well as border security cooperation with Australia. All of these are forms of policy or cooperation to deal with the entry of immigrants on an irregular basis and prevent the dangers of national security including terrorism. The dilemma is, Indonesia is one of the transit countries that is passed by asylum seekers or asylum seekers from various regions in the world who seek protection to Australia.